Gangguan Pola Siklus Haid pada Pesenam di Kota Pekanbaru - Muhammad Muzakir Fahmi; Syamsul Bahri Riva’i; Nurlisis (LPPM Universitas Muhammadiyah Riau, 2020)
The average menstrual cycle obtained in the average menstrual cycle survey results was 29.51 days. Some experienced menstrual cycles of more than 35 days (oligomenore) of 10.29% and menstrual cycles of less than 21 days (polimenore) of 1.5%. There are 26.47% with a duration of menstruation more than 8 days. Furthermore, in the turn of the pads with a mean of 2.99 times per day, replace the pads. But there are some excessive dressing changes (> 3 times), while guessing that you experience excessive menstruation with a percentage of 23.5%. There were 63% of women having menstrual disorders with the highest type of disorder 91.7% of other disorders related to menstruation, followed by menstrual disorders 25%, and menstrual cycle disorders 5%. With the average duration of menstruation obtained at 7.16 days which still includes the normal range of 2 to 8 days. Then research was conducted to find out the dominant factors associated with menstrual cycle pattern disorders. With the aim of analyzing the factors associated with menstrual cycle pattern disturbances in gymnasts in the city of Pekanbaru in 2018. This type of cross-sectional analytic study used a sample of 210 gymnasts in the city of Pekanbaru with inclusion and exclusion criteria. Statistical test uses Bivariate (chi square) and Simple Linear Multivaritic Regression. Variables that are significantly associated with p-value 0.20 is 2.7 times the disease history variable at risk of menstrual cycle pattern disorders.